Threonine Requirement of the Enterally Fed Term Infant in the First Month of Life. Issue 3 (September 2015) - Hogewind-Schoonenboom, Jacomine E.; Huang, Lisha; de Groof, Femke; Zhu, Li; Voortman, Gardi J.; Schierbeek, Henk; Vermes, Andras; Chen, Chao; Huang, Ying; van Goudoever, Johannes B.
Abstract Objective: Threonine is one of the essential amino acids. Its major fate is incorporation into intestinal mucosal proteins and synthesis of secretory glycoproteins. Therefore, it has an important function in the neonatal gut barrier integrity. The objective was to quantify the threonine requirement in fully enterally fed term neonates by means of the indicator amino acid oxidation (IAAO) method, using L-[1-13C]phenylalanine as indicator. Methods: After a 24-hour test diet adaptation, containing randomly assigned amounts of threonine (range 5–182 mg · kg−1 · day−1), the participating neonates received a primed continuous infusion of [13C]bicarbonate and L-[1–13C]phenylalanine. At baseline and during the plateau phase of both infusions, breath samples were obtained for 13CO2. The fractional L-[1-13C]phenylalanine oxidation (F13CO2) was estimated and plotted against the threonine intakes. Biphasic linear regression crossover analysis was used to calculate the breakpoint of the F13CO2, representing the mean threonine requirement. Data are presented as mean ± SD. Results: Thirty-two term neonates (gestational age 39 ± 1 weeks, birth weight 3.3 ± 0.3 kg, mean postnatal age 10 ± 4 days) were studied. The mean threonine requirement was estimated to be 68 mg · kg−1 · day−1 with an upper and lower 95% confidence interval of 104 and 32 mg · kg−1 · day−1, respectively (r2 = 0.37). Conclusions: The determined threonine requirement is extremely close to the existing requirement recommendations (∼90% of the present World Health Organization requirement guidelines). Infant formula preparations presently on the market, however, contain up to twice as much threonine as recommended. The threonine intake in formula-fed infants may therefore be reduced considerably.